Optimization of Soft Skill Competencies and Student Work Readiness Through The MBKM Internship Program at The KIPM Makassar Center - Yanto, Subari; Patang, Patang; Indrayani, Indrayani; Rivai, Andi Alamsyah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to analyze the opportunities and challenges of work practice in preparing Makassar State University students for the world of work, as well as improve their soft skills in communication, discipline, teamwork, and domain-specific knowledge at the Center for Fish Quarantine, Quality Control, and Fishery Product Safety (BB KIPM) as the implementation of the MBKM Curriculum. The four-month research used a descriptive quantitative approach combined with experimental methods, surveys, and in-depth observations to analyze opportunities, challenges, and the impact of work practices on students' soft skills, such as communication, discipline, teamwork, and field-specific knowledge. The findings show that the internship program significantly improves students' practical skills, soft skills, and readiness for the workforce, providing valuable experience in modern laboratory techniques, occupational safety, and industry-specific management practices.